'Articulating value' for clients in a global engineering consulting firm: 'immaterial' activity and its implications for post-knowledge economy expertise. Issue 5 (18th August 2018) - Guile, David; Wilde, Rachel J.
ABSTRACT: Moulier Boutang's book Cognitive Capitalism introduces a radically different conception of the key resources – 'immaterial labour' and 'capture of externalities' – for economic activity, compared with the argument in the knowledge economy discourse that professionals manipulate 'symbols'. The paper explores this claim by firstly, outlining the tenets of Moulier Boutang's argument and explaining why it introduces a new conception of value compared with how that concept is normally defined in neo-classic and Marxist economics. Secondly, explaining why client-facing project teams constitute a paradigmatic example of immaterial activity. Thirdly, makes visible the modes of activity which facilitate the capture of externalities by supplementing Moulier Boutang's concept with Boltanski and Thevénot's ideas about different economies or conceptions of worth. Case study evidence of a global engineering consulting company is then used to identify three expressions of immaterial activity – educative', 'experimental' and 'entrepreneurial' – that assist engineers to articulate their value to clients. The paper concludes by arguing immaterial activity: (i) constitutes a form of expertise that is very different from the prevailing knowledge economy wisdom that knowledge workers manipulate symbols explicitly or tacitly; and, (ii) problematises the sui generis nature of the global 'employability' skills discourse.